Universal Banking and the Development of Secondary Corporate Debt Markets: Lessons from 1830s Belgium - Stefano Ugolini (Norges Bank, 2010)
This paper proposes a reassessment of the old-age debate on universal banking and growth by putting it on a different plan. Modern financial economics are used to provide new theoretical foundations to Gerschenkron's (1962) hypothesis: universality is interpreted as a strategy for banks to reach the critical size needed in order to perform successful securitization of corporate debt. A relevant natural experiment in universal banking and industrialization (Belgium in the 1830s) illustrates the argument. The conclusion is that creating a new financial market also implies establishing intermediaries to supply crucial functions such as underwriting, certification, and liquidity provision.
hdl:11250/2497441
Keywords: G24; G32; N23; O16; 330; universal banking; stock markets; intermediation; financial development